2022
DOI: 10.1186/s12957-022-02644-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinical outcomes according to the time interval between the bridge to surgery stenting and surgery for left-sided malignant colorectal obstruction

Abstract: Background Self-expandable metal stent (SEMS) placement is commonly used as a bridge to surgery (BTS) for left-sided malignant colorectal obstruction (MCO). However, the optimal time interval between BTS stenting and surgery for left-sided MCO is unclear, and the results of previous studies are conflicting. This study aimed to determine the differences in clinical outcomes according to the time interval between BTS stenting and surgery in left-sided MCO. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A retrospective study showed a bridging interval of > 2 weeks between BTS SEMS placement and surgery for LMCO is favorable for short-term clinical outcomes. It can not only form a lower stoma rate but also have a higher rate of laparoscopic surgery (28). In general, a longer interval could compromise surgery by more local tumor infiltration and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study showed a bridging interval of > 2 weeks between BTS SEMS placement and surgery for LMCO is favorable for short-term clinical outcomes. It can not only form a lower stoma rate but also have a higher rate of laparoscopic surgery (28). In general, a longer interval could compromise surgery by more local tumor infiltration and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The later operation group demonstrated better 5-year recurrence-free survival (82.1% vs. 63.2%) and 5-year overall survival (75% vs. 51.4%). Recently, Oh et al 90 formed three groups based on the interval between SEMS use and operation (group 1 [≤2 weeks], group 2 [2–3 weeks], and group 3 [>3 weeks]). In this study, the bridging interval did not affect SEMS-related complications, resection-related complications, 90-day mortality, permanent stoma formation, 3-year disease-free survival, or 3-year overall survival.…”
Section: Optimal Timing Of Surgery After Colon Stentingmentioning
confidence: 99%
“…In this context, another discussed point is the “time to elective surgery,” which is the time between stent insertion and elective surgery[ 18 , 19 ]. Theoretically a delayed interval between SEMS placement and definitive surgery could allow better recovery and improve nutritional status, but it could be burdened by a high rate of local tumor infiltration and fibrosis[ 20 ].…”
Section: Guidelinesmentioning
confidence: 99%